Alterations in the gut microbiota and serum metabolomics of spontaneous cholestasis caused by loss of FXR signal in mice - Wei, Shizhang; He, Tingting; Zhao, Xu; Jing, Manyi; Li, Haotian; Chen, Lisheng; Zheng, Ruimao; Zhao, Yanling (Frontiers in Pharmacology, 2023)
Background: Farnesoid X receptor (FXR) is a key metabolic target of bile acids (BAs) and is also a target for drugs against several liver diseases. However, the contribution of FXR in the pathogenesis of cholestasis is still not fully understood. The purpose of this study is to provide a comprehensive insight into the metabolic properties of FXR-involved cholestasis in mice. Materials and methods: In this study, an alpha-naphthylisothiocyanate (ANIT)-induced cholestasis mouse model and FXR-/- mice were established to investigate the effect of FXR on cholestasis. The effect of FXR on liver and ileal pathology was evaluated. Simultaneously, Untargeted metabolomics combined with 16S rRNA gene sequencing analysis was applied to reveal the involvement of FXR in the pathogenesis of cholestasis. Results: The results showed that ANIT (75 mg/kg) induced marked cholestasis in WT and FXR -/- mice. It is noteworthy that FXR-/- mice developed spontaneous cholestasis. Compared with WT mice, significant liver and ileal tissue damage were found. In addition, 16S rRNA gene sequencing analysis revealed gut microbiota dysbiosis in FXR-/- mice and ANIT-induced cholestasis mice. Differential biomarkers associated with the pathogenesis of cholestasis caused by FXR knockout were screened using untargeted metabolomics. Notably, Lactobacillus_ johnsonii_FI9785 has a high correlation with the differential biomarkers associated with the pathogenesis and progression of cholestasis caused by FXR knockout. Conclusion: Our results implied that the disorder of the intestinal flora caused by FXR knockout can also interfere with the metabolism. This study provides novel insights into the FXR-related mechanisms of cholestasis.